GRAMMATICAL ADJUSTMENT IN NOVEL KALEIDOSCOPE - Marhaendra D, I Gusti Agung Ngurah (Humanis; Volume 16. No. 2. Agustus 2016, 2017)
The title of this paper is “Grammatical Adjustment in Novel Kaleidoscope”. In this paper I try to analyze and discuss the adjustment of grammar in the translation taken from novel Kaleidoscope by Daniele Steel. In analyzing the grammatical adjustment in translation, I applied the theory of Mildered L.Larson in her book entitled Meaning Based Translation as my main theory. I also applied the theory of Catford, in his book entitled A linguistic Theory of translation and supported by other theories that are considered relevant to the topic of discussion. The data of this paper is taken from English novel Kaleidoscope by Daniele Steel and its translation by Therss Susilastuti with the same title. Based on the result of the research and analysis it is found that the grammatical adjustment can be classified into six namely : adjustment from clause into phrase, adjustment from pronoun into noun, adjustment from adjective into noun, adjustment from active into passive, adjustment from passive into active and sentence structure adjustment in translation
Keywords: Grammatical, Adjustment